Experiences and Roles of Community Health Cadres in the Implementation of Integrated Service Posts for Non-Communicable Diseases in Indonesia: A Qualitative Study - Rahmatillah, Irhamni; Usman, Said; nurjannah; Maulana, Teuku; Marthoenis (Asian Journal of Public Health and Nursing, 2025)
Background: Non-Communicable Diseases (NCDs) remain the leading cause of mortality globally and in Indonesia. To address this, Indonesia introduced the Posbindu PTM (Integrated Service Posts for NCDs), a community-based program that relies heavily on volunteer health cadres. This study explores the lived experiences, roles, and challenges faced by these cadres in Banda Aceh. Methods: A qualitative phenomenological approach was used. Twelve female health cadres from Ulee Kareng Health Center were selected using purposive sampling. Semi-structured interviews were conducted in January 2025. Thematic analysis using the Miles and Huberman model revealed two overarching themes and five subthemes, including personal empowerment, logistical constraints, low public participation, and digital limitations. Results: Health cadres reported increased knowledge and confidence in health promotion, but faced critical barriers such as infrastructure limitations, insufficient financial incentives, and community reluctance. Differences in perspectives emerged based on years of service. Notably, cadres with longer tenure (more than five years) expressed greater confidence and skill in engaging the community compared to newer cadres. Conclusion: While cadres derive personal growth and community recognition, system-level changes are essential for program sustainability. Policy recommendations include better government support, consistent training, stakeholder engagement, and adequate resources.